Urgensi Yayasan Pendidikan Ilmu Al-Qur’an Al-Muzahwirah dalam Meningkatkan Kesadaran Beragama Masyarakat Kota Makassar - Dahlan, Muhajir Syawir; Hasibuddin, Hasibuddin; Bachri, Syamsul (Journal of Gurutta Education, 2023)
Religious awareness is the consistency between knowledge and belief in religion as a cognitive element, feelings towards religion as an affective element (this feeling can be seen from one's religious motivation), and religious behavior as a psychomotor element. The purpose of writing this work is to describe the urgency of the Muzahwirah Al-Qur'an Education Foundation to increase the religious awareness of the Community of Kel. Buloa Kec. Tallo City of Makassar. This research method uses descriptive qualitative. Data collection techniques through participatory observation, in-dept interviews, focus group discussions, and documentation. Data analysis techniques through 1) data reduction 2) data presentation; 3) conclusion/verification. The results of the preparation of this work are 1). After participating in learning at the Al-Muzahwirah Al-Qur'an Education Foundation, people are now more aware of religious activities by routinely reading the Al-Qur'an. In Buloa Village, Tallo District, Makassar City, Al-Muzahwirah Al-Qur'an Education Foundation plays an important role in increasing religious awareness. This can be seen from the increase in people's religious awareness as measured by the assessment category and in the various individuals who participated in and won prizes in the competition for reciting the Koran, Hifdzil Al-Qur'an. Because it is more focused on teaching students how to read the Al-Quran, the Al-Muzahwirah Al-Qur'an Science Education Foundation is not very effective in teaching students how to write the Al-Qur'an